2018
DOI: 10.1016/j.ajoc.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Rare corneal complication following selective laser trabeculoplasty

Abstract: PurposeThis case report describes two glaucoma patients who underwent selective laser trabeculoplasty (SLT) and developed a rare post-procedure corneal complication and subsequent permanent corneal distortions and reduced acuity.ObservationsBoth patients experienced early post-procedure corneal edema, reduced visual acuity, and pain. Each patient was treated with topical steroids with resolution of the edema, but each patient had irregular corneal astigmatism which was not present pre-operatively and did not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bettis et al reported a case series of five XFG patients with an IOP spike, two of whom developed corneal decompensation requiring keratoplasty. Several studies have shown minor transient endothelial changes after SLT, such as a reduction in endothelial cell count and central corneal thickness or an increase in dark spots in specular microscopy [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bettis et al reported a case series of five XFG patients with an IOP spike, two of whom developed corneal decompensation requiring keratoplasty. Several studies have shown minor transient endothelial changes after SLT, such as a reduction in endothelial cell count and central corneal thickness or an increase in dark spots in specular microscopy [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Other reported rare complications of SLT are hypopyon with possible herpes simplex reactivation, hyphema, cystoid macular edema in patients with diabetes, and post-ocular trauma. One case reported foveal burns resulting from the use of capsulotomy mode during SLT [ 74 , 75 , 76 , 77 , 78 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Recently, several case reports and small case series have identified a variety of potentially vision-threatening corneal complications of SLT. These include short-term reductions in endothelial cell density, 78 corneal edema (in up to 0.8% of treated eyes 79 ) complicated in some cases by irregular astigmatism, decompensation, and permanent reduction in visual acuity, [80][81][82][83][84][85] keratitis, 86,87 and corneal thinning with permanent hyperopia shifts of up to 6D. 82,84 Evidence for an SLT Dose-Response Relationship Can SLT be performed at a lower energy level and still deliver the efficacy achieved at standard energy?…”
Section: Safety Issues With Standard Sltmentioning
confidence: 99%